Frontiers and Ghettos: State Violence in Serbia and Israel by James Ron (Berkeley: University of California Press, 2003. 208 pages.) (American Journal of Islam and Society, 2006)
Scholars of state violence, among them sociologists and legal scholars, haveinsisted upon the existence of certain distinctions that separate those policemethods deemed acceptable to the international human rights communityfrom those methods of state brutality considered worthy of condemnation.Interestingly, most of the cases that cause confusion over what can be considereda legitimate use of state violence and what is condemned emanate fromthe same places: Serbia and Israel. James Ron’s impressive study of state violenceunder these two modern regimes offers an important genealogical andcomparative analysis of these blurred moral, ethical, and analytical lines.Ron’s work in Frontiers and Ghettos highlights, in particular, patternsof state violence in territories that are under varying degrees of direct statecontrol. These patterns both challenge assumptions about Israeli and Serbianhistory and serve as a corrective to much of the theoretical literature on stateviolence. Ron clearly argues that it is the nature of the state’s formal relationshipwith its territories that ultimately determines the level of state violencein both the Balkans and Palestine. His insight into these patterns is,perhaps, especially persuasive because they are fruitfully compared overdistinct periods of both regions’ history.At the heart of this provocative study is a bravely argued claim that patternsof state violence vary because of international borders and how statesoperate within and beyond them. Ron suggests that geographical and administrativeborders enforce a certain relational order between mechanisms ofcoercion and the extent to which the international community will toleratestate brutality. To make his argument, he carefully outlines how Serbian andIsraeli repertoires of coercion dramatically changed depending upon thenature of each state’s direct relationship with the territories in which theyoperated. In the cases of Serbia’s activities in the former Yugoslavia andIsrael’s actions in Palestine and southern Lebanon, he sees a pattern of ...